1987
DOI: 10.1002/mrm.1910050413
|View full text |Cite
|
Sign up to set email alerts
|

31P magnetic resonance spectroscopy of traumatic spinal cord injury

Abstract: 31P magnetic resonance spectroscopy (MRS) was applied in vivo to study metabolic changes in spinal cord after experimental traumatic injury. Severe trauma, resulting in spastic paraplegia, caused an early and sustained loss of high energy phosphates with profound intracellular acidosis. Early metabolic changes after traumatic spinal injury may predict irreversible tissue damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Phospholipase C activity has also been found to increase after experimental concussive head injury (Wei et al, 1982). Following spinal cord trauma, energy stores are rapidly depleted, with ATP levels falling to less than 20% of normal values (Walker et al, 1977;Anderson et al, 1980;Vink et al, 1987). This would be expected greatly to diminish the rates of FFA reacylation and de novo phospholipid synthesis, which require ATP and other high-energy intermediates (Dawson, 1973;Sun et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase C activity has also been found to increase after experimental concussive head injury (Wei et al, 1982). Following spinal cord trauma, energy stores are rapidly depleted, with ATP levels falling to less than 20% of normal values (Walker et al, 1977;Anderson et al, 1980;Vink et al, 1987). This would be expected greatly to diminish the rates of FFA reacylation and de novo phospholipid synthesis, which require ATP and other high-energy intermediates (Dawson, 1973;Sun et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] This can be attributed largely to the relatively small size of the spinal cord and physiologic pulsation motion at some spinal level sites, which in turn limits our ability to acquire nuclear magnetic resonance (NMR) spectra with adequate signal-to-noise ratio. In particular, only one in vivo study has been reported using 31 P-NMR in animals.…”
mentioning
confidence: 99%
“…In vivo NMR shows great potential for the study of spinal cord morphology and biochemistry, but this application of NMR is limited by the relatively small size of the spinal cord, its deep anatomical locations, and low sensitivity of NMR measurements. The spinal cord has been studied with surface‐coil 1 H imaging (see for example 5 and 1 H and 31 P spectroscopy (6–11). In a recent study, Zelaya el al.…”
mentioning
confidence: 99%